Development and Validation of Gas Chromatography-Triple Quadrupole Mass Spectrometric Method for Quantitative Determination of Regulated Plasticizers in Medical Infusion Sets - So Hyeon Jeon; Yong Pyo Kim; Younglim Kho; Jeoung Hwa Shin; Won Hyun Ji; Yun Gyong Ahn (Journal of Analytical Methods in Chemistry)
A method for the quantitative determination of dibutyl phthalate (DBP), benzyl butyl phthalate (BBP), bis(2-ethylhexyl) adipate (DEHA), bis(2-ethylhexyl) phthalate (DEHP), di-n-octyl phthalate (DNOP), dioctyl terephthalate (DOTP), diisononyl phthalate (DINP), and diisodecyl phthalate (DIDP) in medical infusion sets was developed and validated using gas chromatography coupled with triple quadrupole mass spectrometry (GC-MS/MS) in the multiple reaction monitoring (MRM) mode. Solvent extraction with polymer dissolution for sample preparation was employed prior to GC-MS/MS analysis. Average recoveries of the eight target analytes are typically in the range of 91.8–122% with the relative standard deviations of 1.8–17.8%. The limits of quantification (LOQs) of the analytical method were in the ranges of 54.1 to 76.3 ng/g. Analysis using GC-MS/MS provided reliable performance, as well as higher sensitivity and selectivity than GC-MS analysis, especially for the presence of minority plasticizers at different concentrations.